Extracorporeal photopheresis in heart transplant rejection. Issue 2 (April 2015) - Patel, Jignesh; Klapper, Ellen; Shafi, Hedyeh; Kobashigawa, Jon A.
Abstract: Up to 25% of heart transplant recipients develop rejection requiring intervention. While the majority respond to augmentation of immunomodulatory drug therapy, a subset of patients will remain refractory. Extracorporeal photopheresis (ECP) appears particularly useful in the management of select heart transplant recipients at risk of rejection, with recurrent rejection, or rejection associated with hemodynamic compromise. This chapter summarizes the current clinical experience of ECP in heart transplantation. ECP appears to favorably affect both the cellular and humoral arms of the immune response to the allograft and promote a tolerogenic profile. These immunomodulatory effects also appear to decrease development of cardiac allograft vasculopathy. ECP is generally well tolerated with few adverse effects and low infection risk.